Health complication of repeated abortion among women. - Lamichhane, Urmila (2012)
ABSTRACT: The study entitled ''Health Complication of Repeated Abortion among women'' is mainly based on primary data of married women who used to visit Marie-stopes Centre at Kalanki for abortion and other purpose. The main objectives of this study were to identify basic demographic feature and knowledge of repetition abortion and to find out the cause and practice of repeated abortion and its complication. So the primary data was collected from 30 purposively sampled respondents through interview schedule. Simple statistical techniques were applied for analysis. The study shows that most of women have been practiced repeated abortion and experienced health complication. The educational status of respondents was poor and most of them were housewives. About half of their husbands had higher level of education and they were engaged in service and driving professions. Most of women had knowledge about abortion is legalized but not about criminal abortion. Most of women practiced abortion 2 times and only 3.33 percent women practiced 5 times. Moreover 76.66 percent women had experienced complication of abortion and had experienced physical and mental tension. Among them 39.13 percent women had not checked up their physical complication. About 73.33 percent women had experienced induced abortion, only 6.66 percent were spontaneous. Out of total abortion, 41.66 percent abortions were caused by unwanted pregnancy, 8.33 percent were due to sex selection and only 7.14 percent were due to women's health. About 53.33 percent women didn't know about emergency contraceptive devices, while only 13.33 percent women had used it. Only 23.33 percent women had regularly used family planning contraceptive. In conclusion abortion was the major health problem of women's life. Day by day, incidence of unsafe and repeated abortion has been increasing. Women do so to preserve their respect, prestige and personality in the society. As a result, they were suffering from serious problems from physical and mental complication.